2004
DOI: 10.1109/tmag.2004.832482
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Solutions to Decrease Micro-Fluxgate Sensors Noise

Abstract: Microfluxgate sensors are intended for the measurement of the very small variations of the earth magnetic field. Our sensors would present an output signal with a basic noise of about 1 nanotesla (nT)/ Hz, if an additional noise in the form of instabilities didn't regularly occur, increasing the output noise by regular jumps of 100 nT in the output signal. Some solutions are presented here to reduce and finally to suppress this problematic noise.Index Terms-Magnetic noise, magnetic sensor, magnetic thin film, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
(2 reference statements)
1
0
0
Order By: Relevance
“…The various noise sources have been modeled and their power spectral density estimated from the experimental results. Similar work was performed by Joisten et al (2004). The latest study reported the dc and ac magnetic field dependence of the low-frequency noise in a MEMS flux concentrator device containing a giant magnetoresistance spin valve (Ozbay et al 2006, Edelstein et al 2006.…”
Section: Magnetic Memssupporting
confidence: 61%
“…The various noise sources have been modeled and their power spectral density estimated from the experimental results. Similar work was performed by Joisten et al (2004). The latest study reported the dc and ac magnetic field dependence of the low-frequency noise in a MEMS flux concentrator device containing a giant magnetoresistance spin valve (Ozbay et al 2006, Edelstein et al 2006.…”
Section: Magnetic Memssupporting
confidence: 61%